Distichiasis in Cats - Toebe Gadelha, Alexandre; Rodarte Almeida, Ana Carolina da Veiga; Manera, Juliana Gonzaga Felipe Naves; Mello, Marina Vieira de; Rose, Palloma (Acta Scientiae Veterinariae, 2023)
Background: Distichiasis is a disease that is rare in cats, but very common in dogs. The term distichiasis may be controversial when used in the feline species, given that they do not possess true cilia, but rudimentary hair along the superior palpebra. The patients may be asymptomatic, though some show signs of ocular discomfort and ulcerative keratitis. The diagnosis is reached through an ophthalmological exam, and the treatment consists of the removal of the cilium with or without its hair follicle. With this work, we aim to report a series of cases of distichiasis in cats, as it is an uncommon anomaly, and has the potential to cause ocular discomfort in cats. Cases: Two mobile services of veterinary ophthalmology, one in the federal district of Brasília (DF) and the other in the municipality of Valinhos (SP), attended to 9 cats over a period of 5 years (2018 to 2022). The cats (n = 9) attended are of an undefined breed with ages varying from 10 months to 9 years, with an average of 3.9-year-old. The number of distichiasis presented by the animals was classified according to their quantity, being categorized as a mild grade when there was a single cilium, moderate grade when there were 2 to 4 cilia, and severe grade when there were more than 5 cilia. The highest incidence of distichiasis in this study was in males (78%) while females accounted for (22%) of the cases. The clinical changes reported by the owners consisted of signs of ocular discomfort (photophobia, blepharospasm, and periocular itching), ocular discharge and ocular redness. In the ophthalmological evaluations, blepharospasm (22%), serous to mucosal secretion (56%), chemosis (22%), mild (44%) to moderate (11%) conjunctival hyperemia, and ulcerative keratitis (22%) were observed. Distichiasis was more frequent affecting both eyes (56%), while in only (44%) of cases it affected the left eye only. The highest occurrence of cilia was identified in the upper palpebra (78%). Distichiasis was found more often in the temporal palpebral portion (78%), and in 2 patients the identification was more challenging since these cilia lack pigmentation. Single cilium affected (44%) of patients, while 5 cats had multiple distichiasis (56%). A total of 29% of the cats had a mild grade, whereas 14% had a moderated grade, and 57% had a severe grade. The treatments performed consisted of manual epilation (ME) and electroepilation (EE). ME was carried out in 56% of the cats, with relapses occurring in 80% of the patients, while 44% of the cats submitted to EE had a relapse in 20% of the cases. Discussion: Distichiasis is an inherited disorder very frequent in dogs, but considered uncommon in cats. Its causative factor is still unknown, as is its mode of inheritance. In distichiasis therapy, epilation, electroepilation, electrolysis, diode laser, cryotherapy and surgical palpebral resection techniques are referred to as procedures. Among the treatments used in this study, we observed a lower incidence of relapse with the electroepilation technique, which proved to be a viable and successful therapeutic modality. This series of cases shows that perhaps this disorder is much more frequent than what has been reported in the literature, being sometimes underdiagnosed and consequently underreported. Therefore, distichiasis in cats should be considered as a differential diagnosis in patients with clinical signs of ocular discomfort and ulcerative keratitis. Keywords: cat, ciliary disorders, distichiasis, meibomian gland, epilation, electrocautery. Título: Distiquíases em Gatos Descritores: gato, distúrbios ciliares, distiquíase, glândula meibômio, epilação, eletroepilação.